Beispiel Nr: 23
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(-4/0)\qquad Q(24/0) \\\\ \\ \textbf{Rechnung:} \\ P(-4/0)\qquad Q(24/0) \qquad a=-32 \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=-32(x+4)(x-24)\\ y=-32(x^2- x \cdot 24 +4\cdot x +\left(-4\right)\cdot 24 )\\ y=-32(x^2 -20 x-96) \\ y= -32x^2-640x+3,07\cdot 10^{3} $